Investment Planning Financial Literacy Education in Class I Community Institutions in Medan - Herlin Munthe; Ribka Sari Butar Butar; Dianty Putri Purba; Maya Sabirina Panggabean (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Financial Literacy is an understanding of financial products and concepts with the help of information and advice, as the ability to identify and understand financial risks in order to make the right financial decisions. The method used in data collection is the method of observation and community service activities. In its implementation, the method of discussion and lecture presentation of the material is used. The implementation of community service is carried out on Jl. Correctional Institution No.27, Tj. Gusta, Kec. Medan Helvetia, Medan City, North Sumatra 20125. The results of implementing community service can be concluded: Participants have knowledge related to the level of financial literacy, Participants have the ability to make investment plans for future needs.